2004
DOI: 10.1080/j.1600-0412.2004.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein and homocysteine levels correlate inversely in preeclamptic women in northern Nigeria

Abstract: Background. Preeclampsia/eclampsia is one of the most common complications of pregnancy. It is a cause of high morbidity for both mother and fetus, especially in developing countries. In a recent survey conducted in Gombe, Nigeria, eclampsia was found to be a major cause of maternal mortality (24.2%), second only to obstetric hemorrhage (27.1%). Previous studies have produced contradictory findings regarding total homocysteine (tHcy) levels in women with preeclampsia/eclampsia and there is little information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
(30 reference statements)
2
9
0
2
Order By: Relevance
“…The study was carried out over a period of 1 Those who had diabetes mellitus, chronic hypertension, hepatitis, medical disorders like renal disease, thyroid disease, collagen vascular disease, hemoglobin \8 g%, BMI [30, patients treated for PCOS in past and eclampsia were excluded from the study. Blood sample (5 ml) was collected in EDTA bulb from pregnant and non pregnant women with all aseptic precautions by the qualified staff of O.G Department, S.S.G.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was carried out over a period of 1 Those who had diabetes mellitus, chronic hypertension, hepatitis, medical disorders like renal disease, thyroid disease, collagen vascular disease, hemoglobin \8 g%, BMI [30, patients treated for PCOS in past and eclampsia were excluded from the study. Blood sample (5 ml) was collected in EDTA bulb from pregnant and non pregnant women with all aseptic precautions by the qualified staff of O.G Department, S.S.G.…”
Section: Methodsmentioning
confidence: 99%
“…It is a characteristic multisystem disorder of pregnancy, one of the most common complications of pregnancy and is a leading cause of maternal and perinatal morbidity and mortality [1]. The etiology of preeclampsia is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is a characteristic multisystem disorder of pregnancy, is one of the most common complications of pregnancy and is a leading cause of maternal and perinatal morbidity and mortality [1].…”
Section: Introductionmentioning
confidence: 99%
“…Preterm birth is known to be initiated by multiple mechanisms and various reports have suggested a possibly increased risk for prematurity with very high maternal cholestero l2, 24,25 . Finding by Catov and coworkers 26 showed that an elevation in maternal cholesterol level early in gestation was associated with an increased risk of preterm delivery.…”
Section: Discussionmentioning
confidence: 99%